Consecrated Ground: Spatial Exclusion and the Black Urban Body - Beneventi, Domenico A. (Scripta, 2016)
There has been a long history of discrimination, exclusion, and racial segregation of Canada’s black communities. The establishment and growth of the slave trade, enabled by European maritime technology, made it economically feasible and efficient to establish a trade network of slaves between Africa and the New World. Labour supply in the Americas was affected not only by the lack of Native Americans’ immunity to European diseases, but by European workers’ inability to contend with the extreme heat and tropical diseases in the South American colonies. James Walker argues that contrary to the prevalent understanding that the slave trade was justified by a racialized discourse which constructed the black body inferior to that of whites, “it was the superiority of African labourers in the New World tropics that sealed their fate as slaves” (140).